2014
DOI: 10.1210/jc.2014-1923
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA95 and miRNA190 Are Sensitive Markers for the Differential Diagnosis of Thyroid Nodules in a Caucasian Population

Abstract: We have identified for the first time two miRNAs differently expressed in serum of PTC patients who in combination allow the differential diagnosis of thyroid nodules with great accuracy in our study population. Additional studies are required; however, to define whether these results will also be generalized across other patient populations."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 20 publications
0
47
1
2
Order By: Relevance
“…Cantara et al reported that circulating miRNA95 and miRNA190 were sensitive markers for the differential diagnosis of thyroid nodules in a Caucasian population (MiRNA95 had a sensitivity of 94.9% which reached 100% in a multivariate risk model combined with miRNA190) [10]. Lee et al identified that tumor levels of miR-222 and miR-146b are associated with PTC recurrence and that miR-222 and miR-146b levels in the circulation correspond to the presence of PTC [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cantara et al reported that circulating miRNA95 and miRNA190 were sensitive markers for the differential diagnosis of thyroid nodules in a Caucasian population (MiRNA95 had a sensitivity of 94.9% which reached 100% in a multivariate risk model combined with miRNA190) [10]. Lee et al identified that tumor levels of miR-222 and miR-146b are associated with PTC recurrence and that miR-222 and miR-146b levels in the circulation correspond to the presence of PTC [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several authors [10][11][12] have reported that circulating miRNAs may have potential utility as diagnostic or prognostic markers for thyroid cancers. But to the best of our knowledge, circulating miRNA profiles between non-131 I-avid and 131 I-avid lung metastases form papillary thyroid carcinoma have not been analyzed.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…They also found that miR-146b, miR-155 and miR-222 were slightly higher in patients with lymph node metastasis than in patients without lymph node involvement [80]. The third study identified miR-579, miR-95, miR-29b as being downregulated and miR-190 upregulated in serum of PTC patients compared to patients with nodular goiter (NG) and healthy controls [81]. By combining expression data of miR-95 and miR-190, the authors developed a multivariate risk model which was able to differentiate PTC samples from NGs with 0.99 AUC [81].…”
Section: Endocrine Tumorsmentioning
confidence: 94%
“…The third study identified miR-579, miR-95, miR-29b as being downregulated and miR-190 upregulated in serum of PTC patients compared to patients with nodular goiter (NG) and healthy controls [81]. By combining expression data of miR-95 and miR-190, the authors developed a multivariate risk model which was able to differentiate PTC samples from NGs with 0.99 AUC [81]. In addition, miR-579 and miR-95 were significantly downregulated in PTC compared with NG, while miR-190 was upregulated in PTC both at tissue level and in serum samples.…”
Section: Endocrine Tumorsmentioning
confidence: 99%
“…Kaukázusi népes-ségben ugyanakkor a miR-190 felül-, illetve a miR-95 alulexpresszálódott egészséges emberekhez és jóindulatú elváltozásokhoz viszonyítva [20]. Egy újabb tanulmány-ban a PTC-s betegeket is két csoportra osztották nyirokcsomóáttét megléte alapján.…”
Section: Táblázatunclassified